Establishing baselines for the monitoring and evaluation of regional water security the enhanced water poverty index - Bustamante, Rupert Jeremiah IV Angeles; Arcenas, Agustin L. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
The aims of this thesis are to further develop an index for measuring regional water poverty in the Philippines, to generate baseline information using this tool, to identify water-deprived or at-risk regions based on the results, and to investigate the possible consequences of water poverty on other facets of welfare. The literature consistently points to the disjointed monitoring and evaluation tools and systems employed by the national government as one of the major issues plaguing water resource management in the country; this has led to weak and inadequate planning and prioritization regarding water supply infrastructure investment and other such interventions. A single and simple tool in the form of a Water Poverty Index (WPI) would allow for a more targeted and focused response to the deprivation experienced by households in various water-poor regions. To this end, a development framework involving the consumption of commodities, such as water, in enhancing the capability of a household in terms of aspects of human development was adopted. To reflect this, the WPI was constructed with two main indices (Water Access and Water Quality) and three auxiliary components (Health, Civil Participation, and Standard of Living) based on already existing data. Nine regions were identified as having poor access to water and sanitation, and four others were in danger of falling into that category. Twelve regions received water and sanitation services of poor quality, with three more regions being classified as at risk of experiencing this type of difficulty. These Water Access and Water Quality scores were also found to be highly correlated to the measures of health, productivity, and quality of life. Finally, an Ordinary Least Squares regression with regional interactions was used to determine the regions in need of water supply intervention as well as the corresponding response to the specific water deprivation that each region was experiencing.
Thesis (M.A. Economics) -- University of the Philippines Diliman
Keywords: Water security -- Evaluation -- Philippines; Water poverty index